PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS PROJECT BASED LEARNING PADA MATERI VIRUS TERHADAP HASIL BELAJAR KOGNITIF DI SMA MUHAMMADIYAH 1 JOMBANG - Mufaridha, Lailatul; Rahardjanto, Abdulkadir; Purwanti , Elly; Susetyarini, Roro Eko; Husamah; Hudha, Atok Miftachul; Dita Tri Mulyani (Universitas Cokroaminoto Palopo, 2025)
Virus-related materials can be challenging to comprehend due to its use of scientific and abstract terminology that is often difficult to visualize or directly observe. This difficulty is evident among students at SMA Muhammadiyah 1 Jombang, particularly when learning about the classification and types of viruses. The challenges students face in understanding this material are reflected in their cognitive learning outcomes, which have not yet reached the minimum completeness standard. On average, students' scores are 68, which falls under the